Reported Reasons for Initiating Drug Use among Drug-Dependent Adolescents and Youths in Yunnan, China - Yang, L.; Li, Jianghong; Zhang, Y.; Maycock, Bruce (Informa Healthcare USA, 2009)
Background: As an entry point for illicit drug trafficking, Yunnan was hit hard by the twin epidemics of drug abuse and HIV/AIDS. There are no empirical studies regarding the reasons for initiation of drug use in Yunnan. Objectives: The study investigated the reasons for initiating drug use in drug-dependent adolescents and youths in five regions in Yunnan. Methods: The data were collected in 2004–2005 from a stratified random sample of 467 registered drug addicts under age 25. Pearson chi-square tests were used to analyze the association of reasons for drug use with sociodemographic factors, knowledge of drug related harm, and access to illicit drugs. Results: Curiosity was the most commonly reported reason for initiating drug use and the majority of the respondents reported having little or no knowledge of drug-related harm. The majority of the drug abusers initiated drug use at the age of 13–14 years or younger. Conclusions: There is a potential for sustained educational programs to reduce the high prevalence of adolescent drug use in Yunnan. Scientific Significance: This is the first empirical study that has investigated reasons for initiating drug use based on a random sample of registered drug users in a high risk province of China.